Kinetic control of aqueous polymerization using radicals generated in different spin states - Rintoul, Ignacio (2017)
1) Background: Magnetic fields can interact with liquid matter in a homogeneous and instantaneous way, without physical contact, independently of its temperature, pressure and agitation degree and without modifying recipes nor heat and mass transfer conditions. In addition, magnetic fields may affect the mechanisms of generation and termination of free radicals. This paper is devoted to the elucidation of the appropriate conditions needed to develop magnetic field effects for controlling the kinetics of polymerization of water soluble monomers. 2) Methods: Thermal and photochemically initiated polymerizations were investigated at different initiator and monomer concentrations, temperatures, viscosities and magnetic field intensities. 3) Results: Significant magnetic field impact on the polymerization kinetics was only observed in photochemically initiated polymerizations carried out in viscous media and performed at relatively low magnetic field intensity. Magnetic field effects were absent in polymerizations in low viscosity media and thermally initiated polymerizations performed at low and high magnetic field intensities. The effects were explained in terms of the radical pair mechanism for intersystem crossing of spin states. 4) Conclusion: Polymerization kinetics of water soluble monomers can be potentially controlled using magnetic fields only under very specific reaction conditions.